Deficiency of interleukin-6 receptor ameliorates PM2.5 exposure-induced pulmonary dysfunction and inflammation but not abnormalities in glucose homeostasis - Renzhen Peng; Wenhui Yang; Wenpu Shao; Bin Pan; Yaning Zhu; Yubin Zhang; Haidong Kan; Yanyi Xu; Zhekang Ying (Ecotoxicology and Environmental Safety, 2022)
Background: Ambient fine particulate matter (PM2.5) exposure increases local and systemic interleukin-6 (IL-6). However, the pathogenic role of IL-6 signalling following PM2.5 exposure, particularly in the development of pulmonary dysfunction and abnormal glucose homeostasis, has hardly been investigated. Results: In the study, IL-6 receptor (IL-6R)-deficient (IL-6R-/-) and wildtype littermate (IL-6R+/+) mice were exposed to concentrated ambient PM2.5 (CAP) or filtered air (FA), and their pulmonary and metabolic responses to these exposures were analyzed. Our results demonstrated that IL-6R deficiency markedly alleviated PM2.5 exposure-induced increases in lung inflammatory markers including the inflammation score of histological analysis, the number of macrophages in bronchoalveolar lavage fluid (BALF), and mRNA expressions of TNFα, IL-1β and IL-6 and abnormalities in lung function test. However, IL-6R deficiency did not reduce the hepatic insulin resistance nor systemic glucose intolerance and insulin resistance induced by PM2.5 exposure. Conclusion: Our findings support the crucial role of IL-6 signalling in the development of pulmonary inflammation and dysfunction due to PM2.5 exposure but question the putative central role of pulmonary inflammation for the extra-pulmonary dysfunctions following PM2.5 exposure, providing a deep mechanistic insight into the pathogenesis caused by PM2.5 exposure.